Long‐term trends and seasonal variation in host density, temperature, and nutrients differentially affect chytrid fungi parasitising lake phytoplankton. (24th June 2022) - Gsell, Alena S.; Wolinska, Justyna; Preuß, Katrin; Teurlincx, Sven; Özkundakci, Deniz; Hilt, Sabine; van Donk, Ellen; Ibelings, Bas W.; Adrian, Rita
Abstract: Parasites are generally considered the most commonly occurring type of consumers, yet their biomass and population dynamics are rarely quantified at community level. Here, we used 12 years of weekly or fortnightly monitoring data (518 time points) to determine the occurrence of chytrids, fungal parasites of phytoplankton, to assess their seasonality and long‐term (seasonally‐detrended) dynamics in the pelagic plankton community of a temperate, eutrophic, and polymictic lake. Chytrid infections were observed in c. 75% of all samples with recurrent infections in multiple host taxa. Infection prevalence was highest in spring, but infections occurred throughout the entire year with an average of 2.3 host taxa infected per time point (ranging from 0 to 10 host taxa) and an average infection prevalence of 2.78% (ranging from 0% to 47.35%). Infected host biomass equalled that of the carnivorous zooplankton and decreased over time, while infection prevalence remained unchanged. Seasonal infection prevalence increased with phytoplankton biomass, but decreased with increasing temperature and phosphorus concentrations, reflecting that peak prevalence occurred in spring when temperature and phosphorus concentrations were relatively low. In contrast, seasonally‐detrended prevalence increased with temperature, but decreased with increasing phosphorus concentrations. Chytrids are a common component of the pelagic plankton community with sizeable biomass and removing an—at times—substantial proportion of the primary production, challenging the long‐standing underrepresentation of parasites in ecological studies. Chytrids responded differentially to seasonal variation and long‐term trends in host density, water temperature and nutrient availability, highlighting the need to disentangle seasonal signals from long‐term changes.